Micropropagation of Dendrobium phalaenopsis Orchid Through Overexpression of Embryo Gene AtRKD4 - Setiari, Nintya; Purwantoro, Aziz; Moeljopawiro, Sukarti; Semiarti, Endang (AGRIVITA, Journal of Agricultural Science, 2018)
To increase the efficiency of crop production from Dendrobium phalaenopsis orchids, mass propagation has been performed by inducing somatic embryogenesis through Agrobacterium-mediated transformation of the Arabidopsis embryo gene AtRKD4 into orchid protocorm (developing orchid embryo). The three-week-old protocorms of D. phalaenopsis were genetically transformed with T-DNA carrying 35S :: GAL4 :: AtRKD4 :: GR through A. tumefaciens strain EHA 105. The cultures were maintained in VW medium with 10 mg L-1 Hygromycin. Due to the existence of glucocorticoid response element (GR) in the T-DNA construct, the transformed protocorms were transferred into VW medium with the addition of 15 μM Dexamethasone in 6 weeks after transformation to activate the transgene. A total of 12% protocorms has been confirmed for Hyg + by using PCR. The expression of embryo gene AtRKD4 was confirmed by cDNA analysis using AtRKD4 specific primers and Actin primers as a positive control experiment. The expression level of AtRKD4 in 2.5-month-old D. phalaenopsis transformant shoots was 7 times higher than non-transformant plants, and increased to 86 times higher in 8-months, that much higher than that of non-transformant. These results provide an improved method for genetic transformation of D. Phalaenopsis and will (eventually) increase production efficiency in the future.